NEARNESS TO YOU - Nur Fadhilah Wahid (Iman Publication, 2020)
Nearness To You explores what it means to seek closeness to God in this life through the author’s essays of reflections and contemplations during her travels to meet the seekers of God. While each of our journeys varies, it will eventually lead us back to Him, if only we take a moment to pause and think about God’s presence in our life, our relationship with Him and His endless mercy upon us.